Dietary supplementation of formulated fish specific mineral mixture improved growth and health status of Indian major carps - ANJU VIJAYAN; ABHED PANDEY; UDEYBIR SINGH CHAHAL (Indian Journal of Animal Sciences)
The present study was undertaken to standardize the dose and efficacy of formulated fish specific mineral mixture on survival, growth and health status of Indian major carps (IMC) catla (Labeo catla), rohu (Labeo rohita) and mrigal (Cirrhinus mrigala). The feeding trial (120 days) consists of five treatments (T1-T5, in triplicate), basal diet consisted of rice bran (49-50%), mustard de-oiled cake (48.5-49%), mineral mixture (0-2%) and salt (0.5%), positive control with commercially available mineral mixture (T1) and negative control without any mineral mixture (T2) and three (T3-T5) treatments supplemented with formulated mineral mixture (as per ICAR 2013 recommendations) at three inclusion levels 1%, 1.5% and 2%, respectively. All the water quality parameters were within the acceptable limits. Supplementation of formulated mineral mix in fish feed significantly improved growth performance, feed utilization, haematological parameters and blood metabolic profile whereas, the flesh quality of catla, rohu and mrigal also improved (non-significantly) and recorded best in T4 (formulated mineral mixture at 1.5% of total fish feed) in comparison to positive (T1) and negative (T2) control. The data obtained in the present study will be helpful in increasing the fish production and productivity in sustainable way and in terms enhancing fish farmer’s income and also helping in nutritional security of the nation.